2019
DOI: 10.3390/fluids4020082
|View full text |Cite
|
Sign up to set email alerts
|

A Potential Field Description for Gravity-Driven Film Flow over Piece-Wise Planar Topography

Abstract: Models based on a potential field description and corresponding first integral formulation, embodying a reduction of the associated dynamic boundary condition at a free surface to one of a standard Dirichlet-Neumann type, are used to explore the problem of continuous gravity-driven film flow down an inclined piece-wise planar substrate in the absence of inertia. Numerical solutions of the first integral equations are compared with analytical ones from a linearised form of a reduced equation set resulting from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…In [38], the same boundary condition is derived in real-valued form and where it is demonstrated that it can be decomposed into a Dirichlet and a Neumann boundary condition for Φ. The reduction of the original non-standard boundary condition in Equation (112) containing mixed contributions from different fields u and p to a mathematical standard form has proven to be extremely beneficial for the implementation of numerical methods of solution, as demonstrated in [6,38,74].…”
Section: Integration Of the Dynamic Boundary Conditionmentioning
confidence: 99%
“…In [38], the same boundary condition is derived in real-valued form and where it is demonstrated that it can be decomposed into a Dirichlet and a Neumann boundary condition for Φ. The reduction of the original non-standard boundary condition in Equation (112) containing mixed contributions from different fields u and p to a mathematical standard form has proven to be extremely beneficial for the implementation of numerical methods of solution, as demonstrated in [6,38,74].…”
Section: Integration Of the Dynamic Boundary Conditionmentioning
confidence: 99%
“…Next, by neglecting ∂v y /∂ x compared to ∂v x /∂ y and omitting inertial terms, the set of PDEs is reduced to one that can be solved by successive integration, as shown in detail in [24], leading to the following general solution:…”
Section: Lubrication Approximationmentioning
confidence: 99%
“…a 11 , a 12 , become integrable by: (i) neglecting inertia; (ii) applying an asymptotic analysis, underpinned by the long-wave approximation, as demonstrated in [4] for planar film flows. a 11 , a 12 , become integrable by: (i) neglecting inertia; (ii) applying an asymptotic analysis, underpinned by the long-wave approximation, as demonstrated in [4] for planar film flows.…”
Section: Implementation For Axisymmetric Flowsmentioning
confidence: 99%
“…The two relevant field equations for ψ and Φ, derived as Euler-Lagrange equations of (4) w.r.t. a 11 , a 12 , become integrable by: (i) neglecting inertia; (ii) applying an asymptotic analysis, underpinned by the long-wave approximation, as demonstrated in [4] for planar film flows. Following the same steps as in [4], a single equation for the local film thickness results.…”
Section: Implementation For Axisymmetric Flowsmentioning
confidence: 99%
See 1 more Smart Citation